Profil Swamedikasi Penjualan Obat Anti Inflamasi Non-Steroid (OAINS) Di Apotek Mida Farma Gresik - Helmi Hanifah; Pemta Tiadeka; Riskha Aulia (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2021)
This study aims to determine the profile of self-medication sales of non-steroidal anti-inflammatory drugs at Mida Farma I Drugstore Gresik. It is conducted by using the observational method with data collection and observation on the Non-Steroid Anti-Inflammatory Drug (NSAID) stock cards in February 2020 at Mida Farma I Drugstore Gresik. The results show that the highest sales profile is the non-selective group of 87.68%, then the second is the COX-2 selective group of 12.32%. The most sold drug is ibuprofen of 20% and the lowest sold one is Aspirin of 14%. The pharmacokinetics of ibuprofen are it absorbs very quickly through the stomach; has a maximum plasma level that has reached 1 to 2 hours; and has low side effects